Operationalizing a Behavioral Finance Risk Model: A Theoretical and Empirical Framework - Rassoul Yazdipour; William P. Neace (The Journal of Entrepreneurial Finance (JEF), 2013)
To keep up with the rather fast-growing interest in the discipline of Behavioral Finance and Economics caused in part by the new realities of the post-200S world, and the realities prevailing over three decades before and leading up to that year- there is a discernible need for the production of new generations of testable and yet more realistic models and theories as guides for financial and economic decision makers everywhere. The present work is one such attempt in that direction. This writing first improves upon a recently developed, and real-life-inspired, Behavioral Finance Risk Model (Yazdipour, 2011) and then offers a specific methodology for testing it.
Keywords: D81; G39; M13; 650; Behavioral Finance; Behavioral Economics; Risk and uncertainty; Risk Model